Analisis Kadar Difenhidramin, Dekstrometorfan dan Fenilefrin dalam Sirup Obat Batuk Menggunakan Kromatografi Cair Kinerja Tinggi - Agnes Budiarti; Mukti Tri Utomo; Khoirul Anwar (Universitas Wahid Hasyim Semarang, 2024)
Diphenhydramine hydrochloride, dextromethorphan hydrobromide and phenylephrine hydrochloride are often combined to treat cough. The levels of the three compounds in cough syrup are relatively small, so the analysis requires simultaneous and sensitive methods, one of which is the High Performance Liquid Chromatography (HPLC) method. The purpose of this study is to develop a valid KCKT analysis method to determine the levels of diphenhydramine, dextromethorphan and phenylephrine, apply the validated method to cough syrup and determine the suitability of the levels of the three compounds to the requirements. This study used an isocratic type KCKT (Jazco) with a UV detector at 265 nm, a C₁₈ quiescent phase and a mixed motion phase with phosphate: methanol (30:70, v/v) with a flow rate of 1.0 mL/min. The study produced a value of r= 0.9999 in the linearity test of the three compounds. The sensitivity test produced LOD and LOQ values of diphenhydramine were 0.395 μg/mL and 1.318 μg/mL; The LOD and LOQ of dextromethorphan were 0.642 μg/mL and 2.141 μg/mL; The LOD and LOQ of phenylephrine were 0.177 μg/mL and 0.590 μg/mL. The selectivity test produced a good separation with an R-value of ≥1.5. Precision tests yield %RSD values ≤ 2%. Accuracy tests produce precise retrieval values. The content of the three compounds in the three cough syrup samples met the requirements of the Indonesia Pharmacopoeia. Thus, the developed analysis method meets the requirements of all validation parameters and can be applied.